2023
DOI: 10.5267/j.uscm.2022.12.001
|View full text |Cite
|
Sign up to set email alerts
|

The role of strategic entrepreneurship and social capital on sustainable supply chain management and organizational performance

Abstract: This study aims to examine the effect of entrepreneurial strategy on organizational performance, the effect of social capital on organizational performance with sustainable supply chain management as a mediating variable. Sustainable supply chain management has an important influence on organizational measurement in various industries. It is used in considering environmental impacts and supplier responsibilities. The population in the current study were 390 logistics managers of companies in the manufacturing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Stakeholder involvement in SCM is key for promoting sustainable practices and achieving strategic objectives. Studies have emphasised the significance of collaboration, communication, and teamwork in encouraging sustainable supply chain practices (Wijaya, 2023). Stakeholder theory posits that effective communication between stakeholders and companies can enhance environmental performance and improve sustainable SCM practices (Wijaya, 2023).…”
Section: Sustainable Hrm and Stakeholder Engagement In Scmmentioning
confidence: 99%
See 1 more Smart Citation
“…Stakeholder involvement in SCM is key for promoting sustainable practices and achieving strategic objectives. Studies have emphasised the significance of collaboration, communication, and teamwork in encouraging sustainable supply chain practices (Wijaya, 2023). Stakeholder theory posits that effective communication between stakeholders and companies can enhance environmental performance and improve sustainable SCM practices (Wijaya, 2023).…”
Section: Sustainable Hrm and Stakeholder Engagement In Scmmentioning
confidence: 99%
“…Studies have emphasised the significance of collaboration, communication, and teamwork in encouraging sustainable supply chain practices (Wijaya, 2023). Stakeholder theory posits that effective communication between stakeholders and companies can enhance environmental performance and improve sustainable SCM practices (Wijaya, 2023). However, stakeholder engagement plays a vital role in promoting sustainability knowledge transfer and facilitating the integration of sustainability principles in management education (Amaeshi, Muthuri & Ogbechie, 2019).…”
Section: Sustainable Hrm and Stakeholder Engagement In Scmmentioning
confidence: 99%
“…Owing to the mediating effect on productivity between competitive advantage and a sustainable supply chain management approach, raw material quality is critical to improving the overall performance of the supply chain [17] . In addition, the role of strategic entrepreneurship and social capital in sustainable supply chain management shows how raw material quality influences organizational performance [18] .…”
Section: Economy Dimensionmentioning
confidence: 99%
“…Mondy and Premeaux revealed that "controlling is the process of comparing actual performance with standards and taking any necessary corrective actions" (Ali et al 2017). Sarinah argues that as a management control that can carry out its responsibilities effectively, the supervisory function is (Wijaya and Rifa'i, 2016): To assess whether management controls are adequately suited to be effective. To evaluate whether the results report describes activities that are careful and appropriate.…”
Section: Controllingmentioning
confidence: 99%